The Family Meal Challenge: A Faith-Based Intervention to Empower Families. Issue 3 (July 2018) - Fruh, Sharon M.; Mulekar, Madhuri S.; Crook, Errol; Hall, Heather R.; Adams, James; Lemley, Trey
Abstract : ABSTRACT: African Americans have increased rates of overweight and obesity and are least likely to participate in family meals compared with other racial groups. A Family Meal Challenge (FMC) was developed with the objective of empowering individuals to eat healthy meals together as a family. The FMC was presented through four classes in three churches, two faith-based ministries, and two community service programs in health disparity zip codes. Surveys (N = 257) indicated a positive response. Engaging participants and teaching the benefits of eating healthy family meals in a faith-based environment are feasible and may increase the frequency of family meals. Information is provided to create and implement an FMC in any faith setting.